Effect of impregnation of osmotically dehydrated pineapple with calcium salts by blanching and freezing treatments / Shalini Raja and Saliza Asman - Raja, Shalini; Asman, Saliza (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the effect of calcium chloride (CaCl2) and calcium lactate (CaL) impregnation on osmotically dehydrated (OD) pineapple. Pineapple samples treated with 2.5% w/v CaCl2 and CaL, followed by blanching and freezing, showed consistent functional group and water holding capacity results without any significant differences. Color analysis revealed increased L* and h* values and decreased a* values in all treated-OD pineapple samples. The CaCl2-treated-OD pineapple samples exhibited higher b* and C* values than the CaL-treated-OD pineapple samples, which declined post-blanching and freezing. Sensory analysis indicated significant differences (P<0.05) in overall acceptance influenced by appearance, texture, taste, and odor. Hardness varied significantly (P<0.05) among treated OD samples. However, the blanching and freezing had little adverse effect, indicating no significant difference in the OD pineapple samples. Overall, CaCl2 proved more effective than CaL in preserving the physicochemical and sensory qualities of OD pineapple, suggesting its potential as a superior preservative.